Role of Natalizumab in Relapsing-Remitting Multiple Sclerosis: A review (Journal of Brain and Spine Foundation Nepal, 2021)
Introduction: Multiple sclerosis is a non-traumatic neurological disease caused by an immune-mediated reaction leading to a chronic inflammatory demyelinating disorder of the central nervous system. The treatments for multiple sclerosis are mainly divided into three categories: treatment of exacerbation, slowing disease progression with disease-modifying therapies, and symptomatic therapies. Natalizumab is a monoclonal antibody that works by preventing the adhesion of lymphocytes into the endothelium of the blood-brain barrier, reducing lymphocyte infiltration into the central nervous system. This review aims to study the efficacy and safety of natalizumab in relapsing-remitting multiple sclerosis.Methods: The review was performed using databases like PubMed, Cochrane library, Google scholar from which 48 relevant articles were selected based on the various inclusion criteria. The following keywords were used: “Natalizumab”, “Multiple sclerosis”, “side effects”, “Relapsing-remitting multiple sclerosis”, “progressive multifocal leukoencephalopathy” in different combinations.Results: The literature review suggests that natalizumab reduces the rate of sustained progression of the disease and disability, and was associated with a lower relapse rate in patients with relapsing-remitting multiple sclerosis. However, Progressive multifocal leukoencephalopathy is one of the serious side effects of natalizumab.Conclusion: The literature review suggests that Natalizumab has favorable outcomes in patients with relapsing-remitting multiple sclerosis. Since progressive multifocal leukoencephalopathy is one of the serious side effects of natalizumab, risk stratification should be done.